Utility of bone marrow aspiration in extrapulmonary tuberculosis (Medical Journal of Indonesia, 2002)
This study was undertaken to look for evidence of acid fast bacilli (AFB) in bone marrow (BM) in patients of extrapulmonary tuberculosis. Fifty cases suspected of extrapulmonary tuberculosis underwent bone marrow aspiration from sternum/illiac crest and were put on a therapeutic trial of antituberculosis therapy. All cases taken in the study responded to the therapy. The pattern of involvement were â abdominal (20), CNS (19), pericardial involvement (5), cervical lymphadenopathy (2), PUO (2), spinal (1) and miliary (1). 52% cases showed evidence of AFB in BM (on Ziehl Neelsenâs (ZN) staining) whereas only 4% of cases showed evidence of AFB in any other body fluid (CSF/pericardium/peritonium). Besides this, cytomorphological changes of BM showed evidence of lymphocytosis (22%), increased plasma cells (80%) and prominence of macrophages (88%), thus signifying infective pathology with macrophage overactivity. So we conclude that bone marrow aspiration has a definite diagnostic value and may prove useful when other investigations are unrewarding. (Med J Indones 2002; 11: 148-52) Keywords: bone marrow aspiration, acid fast bacilli, extrapulmonary tuberculosis